The Impact of Interpersonal Communication as a Moderating Variable on the Relationship between Commitment, Discipline, Motivation, and Early Childhood Education Teachers’ Performance - Hariyanti, Dwi Prasetiyawati Diyah; ., Fakhruddin; ., Kardoyo; Arbarini, Mintarsih (Journal of Ecohumanism, 2025)
The early childhood education sector faces increasingly complex challenges in maintaining the quality of teacher performance. This study aims to identify the influence of commitment, discipline, and motivation on teacher performance and understand the role of interpersonal communication as a moderating variable in these relationships. Using survey data from early childhood teachers in Semarang City with a sample of 313 respondents, this study used SmartPLS analysis to test these relationships. The results show that commitment, discipline, and motivation significantly impact teacher performance, with discipline emerging as the strongest direct influence. Interpersonal communication significantly affected performance and moderated the relationship between the independent variables and teacher performance. The study found that communication strengthened the positive effects of discipline and motivation on performance, although it showed a negative moderating effect on the commitment-performance relationship. The findings indicate that educational institutions should develop integrated strategies that combine core competency development with effective communication practices to achieve sustainable improvements in teacher performance.